A comprehensive study of eriocitrin metabolism in vivo and in vitro based on an efficient UHPLC-Q-TOF-MS/MS strategy. Issue 43 (12th August 2019) - Li, Luya; Feng, Xue; Chen, Yuting; Li, Shenghao; Sun, Yupeng; Zhang, Lantong
Abstract : 41 metabolites of eriocitrin in vivo and in vitro was identified based on the efficient UHPLC-Q-TOF-MS/MS strategy. Abstract : Eriocitrin, a main flavonoid in lemons, possesses strong antioxidant, lipid-lowering and anticancer activities and has long been used in food, beverages and wine. However, its metabolism in vivo and in vitro is still unclear. In this study, an efficient strategy was developed to detect and identify metabolites of eriocitrin by using ultra-high-performance liquid chromatography coupled with hybrid triple quadrupole time-of-flight mass spectrometry (UHPLC-Q-TOF-MS) based on online data acquisition and multiple data processing techniques. A total of 32 metabolites in vivo and 27 metabolites in vitro were obtained based on the above method. Furthermore, the main metabolic pathways of eriocitrin included reduction, hydrogenation, N -acetylation, ketone formation, oxidation, methylation, sulfate conjugation, glutamine conjugation, glycine conjugation, desaturation and demethylation to carboxylic acid. This study will lay a foundation for further studies on the metabolic mechanisms of eriocitrin.